Income Tax Progressivity: Trends and Implications. (10th August 2019) - Gerber, Claudia; Klemm, Alexander; Liu, Li; Mylonas, Victor
Abstract: This paper discusses how the structure of the tax system affects its progressivity. It suggests a measure of progressive capacity of tax systems, based on the Kakwani index, but independent of pretax income distributions. Using this and other progressivity measures, the paper (i) documents a decline in progressivity over the last decades and (ii) examines the relationship between progressivity and economic growth. On this relationship, regressions do not reveal a significant impact, suggesting that efficiency costs may be small – at least for degrees of progressivity observed in the sample. Finally, the paper finds that increasing tax progressivity reduces pretax inequality.